Interpretation of Knudsen Cell Experiments to determine the Instant Release Fraction in Spent Fuel Corrosion Scenarios by using a Mechanistic Approach: the Caesium Case. Issue 1665 (2014) - Serrano-Purroy, Daniel; de las Heras, Laura Aldave; Glatz, Jean-Paul; Benes, Ondrej; Colle, Jean Yves; Sureda, Rosa; González-Robles, Ernesto; de Pablo, Joan; Casas, Ignasi; Barrachin, Marc; Dubourg, Roland; Martínez-Esparza, Aurora
ABSTRACT: The Knudsen Effusion Mass Spectrometer (KEMS) and the mechanistic MFPR (Module for Fission Product Release) code are tools which seem particularly interesting to support studies of the Instant Release Fraction (IRF) of Cs from spent nuclear fuel in a final repository. With KEMS, the thermal release of 137 Cs and 136 Xe were analysed by annealing up to total vaporization (2500K) of high burn-up (60 GWd/tU) Spent Nuclear Fuel (SNF) samples. Powder samples from the centre of the fuel, without high burn-up structure, were used. To determine the IRF, samples were analysed before and after being submitted to corrosion experiments in bicarbonated aqueous media. MFPR was applied to determine the localization of Cs and fission gases in the SNF at the end of irradiation; the results are compared and supported by dedicated thermodynamics calculations performed for equilibrium conditions at various temperatures and fuel oxygen potentials by the non-ideal thermodynamic MEPHISTA ( Multiphase Equilibria in Fuels via Standard Thermodynamic Analysis) database. A possible mechanism for Cs release during thermal annealing is proposed, taking into account inter-granular release and Cs oxide vaporization, atomic diffusion, ternary oxide phase formation and bubble release. Differences in KEMS release profiles before and after submitting the samples to aqueous corrosion are attributed to the IRF and to changes in the vaporisation mechanism because of differences in the oxygen potential (pO2 ). The IRF of Cs estimated from the KEMS spectra, consisting on the part located at the grain boundaries and in inter-granular bubbles, is not significantly different from that corresponding to the experimental results found using classical static leaching experiments. New experimental campaigns are being designed to confirm our interpretation proposed after this first run.